Desenvolvimento de hidrogéis neutros e iônicos para a remoção de água livre do biodiesel - Dourado, Marcelo De Luccas, 1993- (2021)
Orientadores: Leonardo Vasconcelos Fregolente, Maria Regina Wolf Maciel